Eastern aspects of M.Kopeev’s works (Journal of Oriental Studies, 2018)
This article is devoted to kazakh and Arabic literature links of XX century on the works of M.Kopeyevand revealed among literary works Arabic motives.Subjectly-compositional structure of the parable in the works of M.Kopeyev compared with analoguesin Arabic literature, Presented studies standing, developing the system of genre of the parable,ways of penetrationand its literary decisions base on national philosophy. And considered arabic sourcesin the works of M.Kopeyev and compared their literary distinction and similarity, revealing the specialtyof the style of M.Kopeyev